Proposal and Evaluation of a Collaborative IS to Support Systematic Reviews and Mapping Studies - Campos, Thiago Prado de; Damasceno, Eduardo Filgueiras; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Systematic Literature Review (SLR) or Systematic Mapping Study (SMS) are a process in which publications dataset is systematically analyzed to cover a research field. These processes involve multiple investigators collaborating to produce more improved work and often use automated tools to facilitate their work. Problem: However, not all tools offer proper support to collaborative SLR or SMS. That is, missing a tool to support the study selection process, allowing the collaboration between researchers by applying individual criteria and collective decision, supported by agreement or discussion and consensus. Solution: We developed the Porifera tool to fill this lack. IS Theory: Technology Acceptance Model (TAM) and a Grounded Theory's phase subset were used to evaluate Porifera's tool quality. Methodology: Undergraduate and postgraduate students enrolled in the Experimental Software Engineering Research,used the Porifera tool and answered a post-used questionnaire with TAM's sentences and other open questions. Then, a quantitative and qualitative analysis was performed. Summary of Results: It was possible to see high perceived usefulness and ease of use for Porifera. Too it noted the effectiveness of resources to support the collaborative activity and its contribution to learning and performing a collaborative SLR or SMS. The evaluation showed points to improve the Porifera's interface. Contribution and Impact in the IS area: The Porifera is an IS for data, information, and knowledge research management because it gathers publications records and allows it will be interpreted and processed, making possible decisions making by researchers. The Porifera also allows performing an SLR or SMS with mobility, knowledge sharing, flexibility, and integration between people and technology.